Juazeiro fruit bending kinetics (Ziziphus joazeiro Mart.) under different concentrations of NaOH - Silva, Jéssica Leite da; Costa, Franciscleudo Bezerra da; Nascimento, Ana Marinho do; Santiago, Mahyara de Melo; Gadelha, Tatiana Marinho (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The objective of this study was to evaluate the ideal amount of sodium hydroxide (NaOH) to be used in the titration breath analysis in juazeiro (Ziziphus joazeiro Mart.) Fruits harvested in the city of Pombal, Paraíba. For this, two volumes of NaOH, 0.5 and 1.0 mL were tested during the 24 hour period. The results demonstrated that the volume of 0.5 mL was efficient only for short periods of analysis, more precisely for up to 16 hours. The results obtained for the volume of 1.0 mL showed to be efficient during the whole period of analysis and become more feasible, because it fixed a greater amount of CO2, when compared to the results obtained when using 0,5 mL of NaOH.